2015
DOI: 10.1186/s12943-015-0383-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of extracellular matrix in cancer is associated with enhanced tumor cell targeting by bacteriophage vectors

Abstract: BackgroundGene therapy has been an attractive paradigm for cancer treatment. However, cancer gene therapy has been challenged by the inherent limitation of vectors that are able to deliver therapeutic genes to tumors specifically and efficiently following systemic administration. Bacteriophage (phage) are viruses that have shown promise for targeted systemic gene delivery. Yet, they are considered poor vectors for gene transfer. Recently, we generated a tumor-targeted phage named adeno-associated virus/phage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Therapies that target the ECM provide a promising approach to overcome chemoresistance either by preventing ECM-conferred chemoresistance or by altering the ECM such that current therapies can overcome physical treatment limits [ 200 , 201 , 202 , 203 , 204 ]. It has been shown that the dense ECM can inhibit therapeutic drug penetration, diffusion and transport, thus the ECM acts as a barrier to drug delivery [ 205 , 206 , 207 , 208 , 209 , 210 , 211 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapies that target the ECM provide a promising approach to overcome chemoresistance either by preventing ECM-conferred chemoresistance or by altering the ECM such that current therapies can overcome physical treatment limits [ 200 , 201 , 202 , 203 , 204 ]. It has been shown that the dense ECM can inhibit therapeutic drug penetration, diffusion and transport, thus the ECM acts as a barrier to drug delivery [ 205 , 206 , 207 , 208 , 209 , 210 , 211 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the phage has evolved to infect bacteria only, with no optimized strategies to deliver genes to mammalian cells. We have investigated various steps of gene delivery upon RGD4C/AAVP vector treatment of cells and found that the main extracellular limiting steps are vector diffusion through the extracellular matrix (ECM) and binding to the cell surface receptors caused by repulsion between the negatively charged phage capsid and mammalian cell surface membranes [ 21 , 22 ]. Following internalization, we reported the endosome/lysosome degradative pathway and proteasome degradation as major intracellular barriers to gene delivery by the vector [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having shown that chemical modification of phage vectors with either CaPi or PEI increases gene delivery efficiency; we next sought to determine whether incorporation of genetic targeting into the vector complexes would lead to further enhancement of gene transfer. Our previously reported phage vectors, AAVP, were initially designed to enter mammalian cells and allow gene expression by ligand display on the phage capsid to bind to specific mammalian receptors [ 23 , 24 ]. The targeting peptide ligand, cyclic RGD4C, was engineered to be displayed on the pIII minor coat protein of phage to allow the vector (RGD4C-phage) to enter mammalian cells expressing αv integrin receptors [ 13 ].…”
Section: Resultsmentioning
confidence: 99%